2013
DOI: 10.1186/1471-2369-14-26
|View full text |Cite
|
Sign up to set email alerts
|

Associations of epicardial fat with coronary calcification, insulin resistance, inflammation, and fibroblast growth factor-23 in stage 3-5 chronic kidney disease

Abstract: BackgroundEpicardial fat, quantified in a single multi-slice computed tomography (MSCT) slice, is a reliable estimate of total epicardial fat volume (EFV). We sought to determine risk factors for EFV detected in a single-slice MSCT measurement (ssEFV) in pre-dialysis chronic kidney disease (CKD) patients. Our primary objective was to determine the association between ssEFV and coronary artery calcification (CAC).Methods94 pre-dialysis stage 3–5 CKD patients underwent MSCT to measure ssEFV and CAC. ssEFV was qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 38 publications
(49 reference statements)
7
38
0
1
Order By: Relevance
“…25, 26 Kerr et al found a positive correlation between urinary albumin to creatinine ratio and single-slice EAT volume in stage 3-5 CKD patients. 25 Cordeiro et al demonstrated that increased EAT volume was a predictor for future CAD events …”
Section: Discussionmentioning
confidence: 99%
“…25, 26 Kerr et al found a positive correlation between urinary albumin to creatinine ratio and single-slice EAT volume in stage 3-5 CKD patients. 25 Cordeiro et al demonstrated that increased EAT volume was a predictor for future CAD events …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the C-terminal portion of FGF-23 is positively associated with increased BMI and insulin resistance as measured by Homeostasis Model Assessment (HOMA), but negatively associated with ferritin and serum iron. (31)(32)(33)(34) Weight loss has been shown to reduce the serum levels of Another study showed that the response of FGF-23 and PTH to a phosphate load is impaired in T2D. (36) This is a new area of investigation, and more studies are needed to define the potential impact of skeletal factors besides osteocalcin on glucose tolerance in both animals and humans.…”
mentioning
confidence: 99%
“…Recent studies showed that the C-terminal portion of FGF-23 is positively associated with increased BMI and insulin resistance as measured by Homeostasis Model Assessment (HOMA), but negatively associated with ferritin and serum iron. (31)(32)(33)(34) Weight loss has been shown to reduce the serum levels of FGF-23. (35) Another study showed that the response of FGF-23 and PTH to a phosphate load is impaired in T2D.…”
mentioning
confidence: 99%
“…Both inflammation and oxidative stress play central roles in the development of atherosclerosis in patients with CKD, and in functional CVD related outcomes, including pathogenesis of LVH, arterial stiffness and global cardiac function [12,13]. Recently the associations between increased EAT thickness, Il-6 and coronary artery calcification (CAC) in patients with CKD stage 3-5 [14] have been demonstrated. Additionally, increasing volumes of EAT in this patient population are associated with an increasing risk of cardiovascular events, independent of general adiposity, and are a better predictor of risk than abdominal visceral adipose tissue [15*].…”
Section: Introductionmentioning
confidence: 99%